Shadow Fields for Deformable Objects - Zhou, Kun; Lin, Stephen; Guo, Baining; Shum, Heung-Yeung (2005)
Soft shadows from deformable objects present a significant challenge for real-time rendering, particularly in dynamic scenes where the arrangement of objects and light sources are continually changing. To address this problem, we propose a technique that computes shadow fields on-the-fly according to the arbitrary changes in the shape of a light source or occluding object. To facilitate run-time shadow field computation, we take advantage of similarities in form among visibility functions sampled along the radial direction to significantly reduce visibility sampling. Because of this property, shadow field samples captured at a single radial distance can be efficiently extrapolated to obtain full shadow field information using precomputed transformation matrices. With this approach, low frequency shadowing effects can be generated in real time for general object motion.